Sosial Media Marketing Untuk Pengembangan UMKM - Riri Putri Dika; Vivi Puspita Sari; Pinta Medina (CV. ITTC INDONESIA, 2023)
Social media marketing is a marketing strategy that involves using social media platforms to promote and develop MSME businesses (Micro, Small and Medium Enterprises). The population of social media users that continues to increase, the use of social media to develop MSME businesses can be a very effective and efficient tool. Therefore, the community service team from Putra Indonesia University